The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1186/1471-2334-13-193
|View full text |Cite
|
Sign up to set email alerts
|

Antibiograms from community-acquired uropathogens in Gulu, northern Uganda - a cross-sectional study

Abstract: BackgroundUrinary tract infections (UTI) are common in clinical practice and empirical treatment is largely employed due to predictability of pathogens. However, variations in antibiotic sensitivity patterns do occur, and documentation is needed to inform local empirical therapy. The current edition of the Uganda Clinical Guidelines recommends amoxicillin or cotrimoxazole as choice drugs for empirical treatment of community-acquired UTI. From our clinical observations, we suspected that this recommendation was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
20
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 28 publications
17
20
1
Order By: Relevance
“…Furthermore, this study showed high sensitivity of bacterial uropathogens 69/83(83.1%) to gentamicin. The sensitivity of gentamicin demonstrated in this study is supported by previous study by Odongo et al (2013). The sensitivity shown by gentamicin in this study is slightly lower than 242.5/351 (69.1%) and 11/18 (61.1%) previously reported by Ali et al (2017) and Kabugo et al (2016) respectively.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, this study showed high sensitivity of bacterial uropathogens 69/83(83.1%) to gentamicin. The sensitivity of gentamicin demonstrated in this study is supported by previous study by Odongo et al (2013). The sensitivity shown by gentamicin in this study is slightly lower than 242.5/351 (69.1%) and 11/18 (61.1%) previously reported by Ali et al (2017) and Kabugo et al (2016) respectively.…”
Section: Discussionsupporting
confidence: 89%
“…In Uganda, the policy of treatment of UTIs was put in place but susceptibility patterns of these bacteria seem to be changing (Kabugo et al, 2016). Most of the previous studies in Uganda by Mwaka et al (2011), Odongo et al (2013), Odoki et al (2015), Katongole et al (2015), Ampaire et al (2015) and Kabugo et al (2016) focused much on the prevalence and antimicrobial susceptibility patterns of bacterial uropathogens neglecting MDR factors associated with these bacteria and their phylogenetic groups. Khawcharoenporn et al (2013) reported that, Infectious Diseases Society of America recent guidelines recommended that treatment of UTIs using antimicrobial therapy should be directly proportional to indigenous resistance profile of bacteria, drug availability and antimicrobial intolerance/allergy history of treated patients (Gupta et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Resistance to cotrimoxazole, amoxicillin/clavulanic acid and ciprofloxacin is far above the 20% rate recommended for empirical use of antibiotics for communityacquired UTIs. 26 This result is consistent with findings from other studies in Uganda 27 and Buea 6 . Such high levels of resistance are probably due to antibiotic misuse by poorly trained health workers as has been documented in many developing countries.…”
Section: Discussionsupporting
confidence: 83%
“…In this study, higher resistance rates to all antibiotics tested with the exception of imipenem and nitrofurantoin may be expounded by the high and uncontrolled usage of these antibiotics, especially third-generation cephalosporins, during the past few years in the country (20,21). Unfortunately, these antibiotics have been widely prescribed not only for urinary tract infections but also for other infections in Uganda (22) .…”
Section: Discussionmentioning
confidence: 86%